2019
DOI: 10.3390/electronics8090959
|View full text |Cite
|
Sign up to set email alerts
|

Ship Target Detection Algorithm Based on Improved Faster R-CNN

Abstract: Ship target detection has urgent needs and broad application prospects in military and marine transportation. In order to improve the accuracy and efficiency of the ship target detection, an improved Faster R-CNN (Faster Region-based Convolutional Neural Network) algorithm of ship target detection is proposed. In the proposed method, the image downscaling method is used to enhance the useful information of the ship image. The scene narrowing technique is used to construct the target regional positioning networ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 21 publications
0
42
0
Order By: Relevance
“…An et al [20] suggested an improved RBox-based target detection framework to obtain accuracy recall rate and precision of the detection. Qi et al [21] Improved Faster-RCNN by completing image downscaling to obtain useful information of ship images, which helps in the accurate and timely detection of ship images. Zhang et al [22] Proposed a lightweight optimization network LFO net based on SSD for ship detection in SAR images.…”
Section: It Is Fastmentioning
confidence: 99%
See 1 more Smart Citation
“…An et al [20] suggested an improved RBox-based target detection framework to obtain accuracy recall rate and precision of the detection. Qi et al [21] Improved Faster-RCNN by completing image downscaling to obtain useful information of ship images, which helps in the accurate and timely detection of ship images. Zhang et al [22] Proposed a lightweight optimization network LFO net based on SSD for ship detection in SAR images.…”
Section: It Is Fastmentioning
confidence: 99%
“…Inland waterways have become major means of transportation in many parts of the world as reported by different researchers [8,17,21]. However, transportation in these waterways is faced with different challenges-such as collisions-which can result in accidents and death of people.…”
Section: Motivationmentioning
confidence: 99%
“…In view of the problems that the decimal point of digital instrument in the actual scene of substation is prone to false detection and leak detection, and the accuracy of number identification is not high. The paper innovatively combines Faster R-CNN [13][14][15] and YOLOv4 [16] target detection algorithms with connected domain analysis methods. A target detector was formed, and experiments were carried out on the image data actually collected by the substation and compared with the detector composed of Faster R-CNN and YOLOv4.…”
Section: Related Workmentioning
confidence: 99%
“…To implement real-time ship detection, Qi et al proposed an improved Faster R-CNN algorithm by scene reduction technology to reduce the target scale during searching [32]. Lin et al proposed a new network for ship detection in SAR Images based on the Faster R-CNN, which improved the detection performance and execution speed through squeeze and excitation mechanisms [33].…”
Section: Related Workmentioning
confidence: 99%